The Actual Benefit Gaining and Presumptive Impoverishment of the Impoverished Person in the Hypothesis of Usage of Another’s Property in the Meaning of Article 59 of the Obligations and Contracts Act - Malinov, Ivaylo (Yearbook of the Law Department, 2021)
The present article examines the problems arising in one of the specific hypotheses of the general claim for unjust enrichment within the meaning of Art. 59 of the Obligations and Contracts Act. In the predominant part of the practice, the courts do not examine in detail the question of whether the impoverished plaintiffs had the intention at all and whether they would objectively receive the property benefits appropriated by the unauthorized person using the foreign item. In this way the practice literally creates an “objective” unjustified enrichment in the presence of usage of someone else‘s property without legal grounds and an established right of ownership of the plaintiff. Further developing this scenario leads to a situation in which the court does not examine whether the plaintiff actually suffered impoverishment, despite the explicit requirement of the norm of Art. 59, para. 1 of the Obligations and Contracts Act for the presence of such as part of the elements of the factual composition of the norm. The indicated tendency of the judicial practice will be the examined subject of analysis in the following article.